2021
DOI: 10.1039/d1ra04478h
|View full text |Cite
|
Sign up to set email alerts
|

New biomaterials for Ni biosorption turned into catalysts for Suzuki–Miyaura cross coupling of aryl iodides in green conditions

Abstract: New biomaterials were functionalised for biosorption of Ni from aqueous solutions and valorised as ecocatalysts in Suzuki–Miyaura green reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The Grison group has shown that the remediation phytotechnologies, such as phytoextraction [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], rhizofiltration [ 28 , 29 , 30 , 31 ] and biosorption [ 32 , 33 , 34 , 35 , 36 ] generate biomass which can be turned into innovative ecocatalysts. Among the plant species that can be transformed, here, we selected the ones that were the richest in potassium ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Grison group has shown that the remediation phytotechnologies, such as phytoextraction [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], rhizofiltration [ 28 , 29 , 30 , 31 ] and biosorption [ 32 , 33 , 34 , 35 , 36 ] generate biomass which can be turned into innovative ecocatalysts. Among the plant species that can be transformed, here, we selected the ones that were the richest in potassium ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This innovative methodology is based on the use of biomass derived from metal-hyperaccumulating plants, used in the phytoextraction of metal contaminated sites, for the preparation of polymetallic catalysts suitable for applications in organic synthesis. This concept was successfully applied for important transformations such as the Lewis and/or Brønsted acid-catalyzed reactions (Diels–Alder reaction, Friedel–Crafts reaction, multicomponent reactions, cascade reactions) [ 54 , 55 , 56 , 57 , 58 ]; coupling reactions (Suzuki, Heck, Sonogashira and Ulmann type reactions) [ 59 , 60 , 61 , 62 , 63 , 64 ]; reductions (aminoreduction, selective reduction of αβ-unsaturated carbonyl compounds, nitro- and halogeno arenes) [ 65 , 66 , 67 ]; oxidations (epoxidations, oxidative cleavage, oxidations of alcohols) [ 68 , 69 , 70 ]; and tandem reactions (tandem carbonyl-ene cyclization, synthesis of substituted pyridines and oxidative iodination of ketones) [ 71 , 72 , 73 ]. However, examples on the use of ecocatalysis for C-P bond formation have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The Grison group has shown that remediation phytotechnologies, such as phytoextraction [ 30 , 31 , 32 ], rhizofiltration [ 33 , 34 , 35 ] and biosorption [ 35 , 36 , 37 , 38 ], generate biomass rich in transition metals that can be turned into innovative catalysts, called ecocatalysts [ 39 , 40 , 41 ]. Using the concept of ecocatalysis, we advanced the aim that only natural or biosourced catalysts would be used for preparing the cyclic oxyterpenes.…”
Section: Introductionmentioning
confidence: 99%